2018
DOI: 10.1111/bcpt.13124
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐sensitive reversible and time‐dependent CYP2D6 inhibition in human liver microsomes

Abstract: Cytochrome P450 (CYP) 2D6 metabolizes a wide range of xenobiotics and is characterized by a huge interindividual variability. A recent clinical study highlighted differential magnitude of CYP inhibition as a function of CYP2D6 genotype. The aim of this study was to investigate the effect of CYP2D6 genotype on the inhibition of dextromethorphan O-demethylation by duloxetine and paroxetine in human liver microsomes (HLMs). The study focused on genotypes defined by the combination of two fully functional alleles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…So, genetic polymorphisms in drug-metabolizing enzymes can affect the occurrence of phenoconversion induced by drug inhibitors. As reported by Storelli et al, differences in CYP2D6 inhibition observed in vitro with paroxetine (mechanism-based inhibitor) or duloxetine (competitive inhibitor) across CYP2D6 genotypes were not related to their inhibition parameters but likely due to a differential level of functional enzymes as a function of the CYP2D6 genotype [57,58].…”
Section: The Case Of Mirabegronmentioning
confidence: 56%
“…So, genetic polymorphisms in drug-metabolizing enzymes can affect the occurrence of phenoconversion induced by drug inhibitors. As reported by Storelli et al, differences in CYP2D6 inhibition observed in vitro with paroxetine (mechanism-based inhibitor) or duloxetine (competitive inhibitor) across CYP2D6 genotypes were not related to their inhibition parameters but likely due to a differential level of functional enzymes as a function of the CYP2D6 genotype [57,58].…”
Section: The Case Of Mirabegronmentioning
confidence: 56%
“…In PMs, the CYP2D6 protein is absent and therefore the CYP2D6 abundance of PM subjects is set to zero. However, immunologic and proteomic studies failed to demonstrate a difference in the amounts of CYP2D6 between activity scores 0.5 to 2, which seems to be mostly related to the high interindividual variability, even within a same genotype. Therefore, there was no evidence supporting a change of functional CYP2D6 abundance for non‐PM genotypes, and we rather decided to incorporate the effect of genetic polymorphisms on CYP2D6 enzyme kinetics data (intrinsic clearance (CLint) or maximal reaction velocity (V max )).…”
Section: Discussionmentioning
confidence: 87%
“…The optimized model predicted well CYP1A2 contribution in hepatic clearance, as verified with a DDI trial with the potent inhibitor fluvoxamine in male smokers . Duloxetine has been shown to increase the exposure of the CYP2D6 substrates desipramine and tolterodine up to 2.9‐fold with a 60 mg twice‐daily regimen, which could not be predicted by the bottom‐up approach in Simcyp using experimental Ki values in the range of 2–4 μM . Instead, this value was optimized from in vivo DDI data with desipramine and verified with a set of independent DDI data with desipramine, metoprolol, and tolterodine .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations